The characteristics approximation of nonlinear elements in parametrical transformers, working in superior zones of instability of oscillations - L.V. Cherckesova (Advanced Engineering Research, 2009)
In the article is looked the questions of the approximation of characteristics of nonlinear element in parametrical devices of different kinds, working superior zones of instability of oscillations. In this work there were calculated coefficients of different approximating function (of hyperbolic sinus and other functions). The results that were received with aid of different approximating functions were compared with real experimental curve.